Resistance to Cetuximab in EGFR-Overexpressing Esophageal Squamous Cell Carcinoma Xenografts Due to FGFR2 Amplification and Overexpression - Yi Zhang; Tiecheng Pan; Xiaoxuan Zhong; Cai Cheng (Elsevier, 2014)
Esophageal carcinoma is one of the most virulent malignant diseases and a major cause of cancer-related deaths worldwide. Despite improvements in surgical techniques and perioperative management and surgery combined with chemotherapy and/or radiotherapy, the prognosis of esophageal squamous cell carcinoma (ESCC) at an advanced stage remains poor. ESCC shows a relatively high incidence of EGFR (50% - 70%), and the humanized monoclonal antibody (mAb) cetuximab against EGFR has been undergoing clinical development. However, all responding patients eventually developed acquired resistance to cetuximab. In the current study, we described a cetuximab-sensitive ESCC xeongraft model that developed resistance to cetuximab as a result of FGFR2 gene amplification and overexpression. Inhibition of FGFR2 signaling in this xenograft model restored its sensitivity to cetuximab. The antitumor effect may be induced by inhibition of AKT phosphorylation. These findings suggest that combination therapy including cetuximab and FGFR2 inhibition may be a promising strategy to treat ESCC. Keywords:: EGFR, FGFR2, cetuximab, esophageal squamous cell carcinoma